Heat transfer model for gas-liquid slug flows under constant flux - Walsh, P; Walsh, E; Muzychka, Y (2010)
This paper investigates the mechanisms leading to enhanced heat and/or mass transfer rates in two-phase non-boiling slug flows. The problem is analyzed in a minichannel geometry subjected to a constant heat flux boundary. Local Nusselt numbers, obtained using Infrared thermography are analyzed in both entrance and fully developed flow regions. These novel measurements highlight the physics governing slug-flow heat transfer and results indicate that optimized slug geometries can yield up to an order of magnitude heat transfer enhancement. Finally, based on the physics identified, a heat transfer model is developed which is also applicable to similar mass transfer problems. © 2010 Elsevier Ltd. All rights reserved.